Intussusception with ischemia secondary to Meckel's Diverticulum in a 13 year old - Charlotte Ferrier; Kate Johnson; Stephen Clifforth (Elsevier, 2021)
This case demonstrates a rare presentation of a 13 year old boy who attended a rural Emergency Department with severe epigastric pain, nausea and vomiting. On arrival he was hypertensive and clinical examination found him to have tenderness most pronounced in the right iliac fossa leading to presumed diagnosis of appendicitis. However, upon surgical review it was felt his clinical examination and symptoms were inconsistent with those typically found in acute appendicitis.Ultrasound and abdominal x-ray were performed which did not clearly identify a cause for the patient's presentation however formal reports were not readily obtainable as this occurred after hours at our rural facility. Due to his clinical appearance and a significantly raised white cell count the decision was made to perform a diagnostic laparoscopy as it was evident he had a serious intra-abdominal pathology.Intra-operatively we determined the patient to have ischaemic bowel secondary to intussusception. Following resection of the affected bowel we identified an inverted Meckel's diverticulum to have been the lead point. This case is of clinical significance due to its unclear initial presentation as well as the patient being beyond the normal age range for both intussusception and symptomatic Meckel's Diverticulum.